Gamification to Improve Participation in an Environmental Science Course: An Educator’s Reflection - Tang, Kuok Ho Daniel (Acta Pedagogia Asiana, 2023)
Reticence prevalent among East Asian students has prompted educators to attempt different methods to engage them. Gamification of courses has gained popularity as an avenue to encourage students’ participation, and it is facilitated by the roll-out of diverse online gamification platforms. This study aims to reflect on an educator’s experience of incorporating elements of gamification in an environmental science course delivered in a micro-campus established through a Sino-American educational collaboration. Gibb’s Reflective Cycle was adopted to guide the reflection practice. Gamification was implemented with three online interactive platforms, namely Poll Everywhere, Kahoot, and Quizizz. Poll Everywhere was mainly used for short polls and activities during lessons, while Kahoot and Quizizz were used for quiz-like competitions whose scores did not contribute to students’ grades. Kahoot created a lively atmosphere in class but was constrained by limits on players’ numbers, internet control, and the lag between sending and receiving responses. Quizizz had more game elements, which thrilled individual players but was less able to create the lively classroom the educator desired. It was more stable, perhaps because it was less subjected to internet control. Poll Everywhere had a less attractive scoreboard and was more appropriate for short classroom activities. Students' interest in the platforms tended to wane with each repeated use of the platforms. To improve the gamification experience, a mix of platforms could be used, and locally developed platforms could be sourced for stability and diversification.